2015
DOI: 10.1007/s11164-015-2290-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of 1,3,4-oxa(thia)diazole, 1,2,4-triazole-5-(thio)one and S-substituted derivatives of 3-((2-carboxyethyl)phenylamino)propanoic acid

Abstract: A series of novel derivatives of 3-((2-carboxyethyl)phenylamino)propanoic acid bearing two identical substituted 1,3,4-oxadiazole, 1,3,4-thiadiazole, or 1,2,4-triazole moieties were synthesized and their molecular structures were confirmed by IR, 1 H, 13 C NMR spectroscopy, and elemental analysis data. The synthesized compounds were screened for their reducing power, free radical scavenging, plant growth regulating, and antimicrobial properties. 5,5 0 -((Phenylazanediyl)bis(ethane-2,1-diyl))bis(4-phenyl-2,4-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…By employing the most often used method for the synthesis of hydrazone-type compounds, i.e., the reaction of hydrazides with carbonyl compounds, Schiff bases 28 – 37 were synthesized by condensation reaction of 1 and corresponding disubstituted ketones in methanol at reflux temperature of the reaction mixtures [ 19 , 21 ]. The 1 H-NMR spectra for these compounds display double sets of resonances of the CO–NH group protons with signal intensity ratio 0.6 : 0.4 due to the restricted rotation around the amide bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing the most often used method for the synthesis of hydrazone-type compounds, i.e., the reaction of hydrazides with carbonyl compounds, Schiff bases 28 – 37 were synthesized by condensation reaction of 1 and corresponding disubstituted ketones in methanol at reflux temperature of the reaction mixtures [ 19 , 21 ]. The 1 H-NMR spectra for these compounds display double sets of resonances of the CO–NH group protons with signal intensity ratio 0.6 : 0.4 due to the restricted rotation around the amide bond.…”
Section: Resultsmentioning
confidence: 99%
“…As a continuation of our interest to further explore the structure-activity relationship of the biologically active derivatives of amino acids and nitrogen-containing heterocyclic compounds [ 18 , 19 , 20 ], we report herein the synthesis of a series of 1-(5-chloro-2-hydroxyphenyl)-5-oxopyrrolidine-3-carboxylic acid derivatives bearing heterocyclic moieties and evaluation of their antioxidant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation reactions of acid hydrazides with aliphatic diketones provide five-membered heterocyclic compounds [ 25 , 26 ]. Thus, pyrrole derivative 12 was obtained from hydrazide 9 by refluxing it with hexane-2,4-dione in propan-2-ol in the presence of acetic acid for 2 h. Reaction of 9 with pentane-2,5-dione in the presence of concentrated HCl at reflux temperature afforded pyrazole derivative 13 in 82% yield over 5 h. The reaction was much faster (20 min), when the reaction mixture was subjected to microwave irradiation at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For example, triazoles are an important functionality of pharmaceutical agents with many diverse biological activities (Arfan et al, 2018;Patel, Khan, Rajani, 2010). Remarkably, the biological activity profile of the compounds contains azole antifungal drugs (Iqbal et al,2020;Sekhar et al,2019;Çavusoglu, Yurttas, Cantürk, 2018; Yang L, Synthesis, antimicrobial and antioxidant activities of pyridyl substituted thiazolyl triazole derivatives Bao XP, 2017;Tumosienė et al, 2016;Mange et al, 2013;Panda, Jain, 2014). However, the widespread use of triazoles increased the resistance and hepatotoxicity formation, which is a current problem (Gaikwad, Patil, Bobade, 2012;Kharb, Sharma, Sharma, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was observed that sulfur linked 1,2,4-triazole compounds were relatively efficient antimicrobial agents without resistance (Turan-Zitouni et al, 2005;Shiradkar et al, 2007;Jalilian et al, 2000;Rostami, Manesh, Samie, 2013;Sun et al, 2014). In addition, a large number of synthesized 1,2,4-triazole derivatives were reported and associated with significant antioxidant activities (Bindu, Vijayalakshmi, Manikandan, 2020;Kaddouri Y et al, 2020;Dorovic et al, 2019;Koparir, 2019;Tumosienė et al, 2019;Tumosienė et al, 2018;Behalo, Amine, Fouda, 2017;Tumosienė et al, 2016) The thiazole systems, which are known to have an antimicrobial activity are also effective azole rings.…”
Section: Introductionmentioning
confidence: 99%